Pod indehiscence in common bean is associated with the fine regulation of PvMYB26. (28th November 2020) - Di Vittori, Valerio; Bitocchi, Elena; Rodriguez, Monica; Alseekh, Saleh; Bellucci, Elisa; Nanni, Laura; Gioia, Tania; Marzario, Stefania; Logozzo, Giuseppina; Rossato, Marzia; De Quattro, Concetta; Murgia, Maria L; et al.
Abstract : Linkage mapping and histological and expression pattern analyses in pods identified PvMYB26 as the best candidate gene for pod indehiscence, mediated by a non-functional abscission layer in the pod. Abstract: In legumes, pod shattering occurs when mature pods dehisce along the sutures, and detachment of the valves promotes seed dispersal. In Phaseolus vulgaris (L)., the major locus qPD5.1-Pv for pod indehiscence was identified recently. We developed a BC4 /F4 introgression line population and narrowed the major locus down to a 22.5 kb region. Here, gene expression and a parallel histological analysis of dehiscent and indehiscent pods identified an AtMYB26 orthologue as the best candidate for loss of pod shattering, on a genomic region ~11 kb downstream of the highest associated peak. Based on mapping and expression data, we propose early and fine up-regulation of PvMYB26 in dehiscent pods. Detailed histological analysis establishes that pod indehiscence is associated with the lack of a functional abscission layer in the ventral sheath, and that the key anatomical modifications associated with pod shattering in common bean occur early during pod development. We finally propose that loss of pod shattering in legumes resulted from histological convergent evolution and that it is the result of selection at orthologous loci.